The setting pass and performance indices in Volleyball - Laios, A.; Moustakidis, A. (International Journal of Performance Analysis in Sport, 2011)
The present article focuses primarily on the effect of the setter's choice on the outcome of the attack. The sample was comprised from the matches of the final four of the 2009 C.E.V. Champions League held in Prague and of the final four of the 2009 C.E.V. Cup held in Athens. The total number of phases analyzed was 1472. After a perfect reception the setter makes a right choice when the he chooses the center spiker only when the opposing center blocker is out of position or time to attempt the block, otherwise the pass goes to an outside hitter. Conversely, a wrong choice is when the center is blocked and he receives the pass, or when the center is free and he does not receive the pass. Results have shown that the setters make the right choice only in half the cases and this has a significant impact on the team's attack efficiency, especially in the case of quick attacks. Setters can be trained to improve their peripheral vision, so that they can track simultaneously the trajectory of the ball coming from the reception, and the relative timing (or better its absence) of the middle hitters and blockers.